2017
DOI: 10.1161/jaha.117.005983
|View full text |Cite
|
Sign up to set email alerts
|

Role of Total, Red, Processed, and White Meat Consumption in Stroke Incidence and Mortality: A Systematic Review and Meta‐Analysis of Prospective Cohort Studies

Abstract: BackgroundPrevious meta‐analyses on meat intake and risk of stroke did not report the effect of white meat (poultry meat, excluding fish) and did not examine stroke incidence and mortality separately. We aimed to investigate the relationship of total (red and processed meat), red (unprocessed or fresh red meat), and processed (processed red meat) consumption along with white meat on risk of stroke incidence and mortality.Methods and ResultsArticles were identified from databases and reference lists of relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
89
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 54 publications
8
89
2
1
Order By: Relevance
“…Substituting red meat with high-quality plant protein sources, but not e.g., low-quality carbohydrates, leads to favorable changes in blood lipids and lipoproteins [70]. Meta-analyses of prospective studies have reported positive associations between red meat intake and an increased risk of stroke and type 2 diabetes (T2D) [71][72][73], and both red meat and processed red meat have been associated with all-cause mortality [74] and with cardiovascular disease mortality [75]. Others, e.g., Zeraatkar et al, conclude that the magnitude of associations is small and the certainty is low, although same overall results were found in meta-analyses on cohort studies, i.e., reduced intake of unprocessed red meat intake was associated with reduction in risk for cardiovascular mortality, stroke, myocardial infarction (MI), and T2D; and reduced intake of processed meat intake was associated with decrease in risk for all-cause mortality, cardiovascular mortality, stroke, MI, and T2D [76].…”
Section: Discussionmentioning
confidence: 99%
“…Substituting red meat with high-quality plant protein sources, but not e.g., low-quality carbohydrates, leads to favorable changes in blood lipids and lipoproteins [70]. Meta-analyses of prospective studies have reported positive associations between red meat intake and an increased risk of stroke and type 2 diabetes (T2D) [71][72][73], and both red meat and processed red meat have been associated with all-cause mortality [74] and with cardiovascular disease mortality [75]. Others, e.g., Zeraatkar et al, conclude that the magnitude of associations is small and the certainty is low, although same overall results were found in meta-analyses on cohort studies, i.e., reduced intake of unprocessed red meat intake was associated with reduction in risk for cardiovascular mortality, stroke, myocardial infarction (MI), and T2D; and reduced intake of processed meat intake was associated with decrease in risk for all-cause mortality, cardiovascular mortality, stroke, MI, and T2D [76].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Subjects without prediabetes had a greater intake of meat, and the main type of meat may be white meat. A systematic review reported that white meat could reduce the risk of cardiovascular disease, which is significantly associated with diabetes mellitus 19,20 . Moreover, the excessive consumption of processed red meat is associated with a higher incidence of diabetes and undetected diabetes mellitus 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Excessive consumption of meat and animal products may be deleterious to human health (with meta-analytic evidence regarding cancer [1][2][3][4], cardiovascular disease [5][6][7], metabolic disease [8][9][10], obesity [11], stroke [12], and all-cause mortality [13], albeit sometimes subject to methodological limitations), promotes the emergence and spread of antibiotic-resistant pathogens [14], is a major source of greenhouse gas emissions and environmental degradation [15], and contributes to market demand for industry practices that cause the preventable suffering of more than one billion animals in the USA annually [16]. Therefore, developing simple, effective interventions to reduce meat consumption could carry widespread societal benefits.…”
Section: Introductionmentioning
confidence: 99%